Local government grants for private schools - Justyna Orlikowska (Prawo Budżetowe Państwa i Samorządu)
This article aims to analyze the educational grants from budget of local government. Author presented procedures about establish private schools and educational institutions and explained selected concepts about units of education. The article presents selected judgment from SN and NSA in disputes about grants for private schools.